FEK self‐assembled peptide hydrogels facilitate primary hepatocytes culture and pharmacokinetics screening. Issue 9 (18th March 2022) - He, Ting; Qiao, Shida; Ma, Chen; Peng, Zhaoliang; Wu, Zhitao; Ma, Chenhui; Han, Li; Deng, Qiangqiang; Zhang, Tianwei; Zhu, Yishen; Pan, Guoyu
Abstract: A FEFEFKFK (FEK, F, phenylalaninyl; E, glutamyl; K, lysinyl)‐based self‐assembling peptide hydrogel (FEK‐SAPH) was developed to replace sandwich culture (SC) for improved culture of primary hepatocytes in vitro. Under neutral conditions, FEK self‐assembles to form β‐sheet nanofibers, which in turn form FEK‐SAPH. For the culture of rat primary hepatocytes (RPH), the use of FEK‐SAPH simplified operation steps and promoted excellent cell–cell interactions while maintaining the SC‐related RPH polarity trend. Compared with SC, FEK‐SAPH cultured RPH for 14 days, the bile duct network was formed, the secretion of albumin and urea was improved, and the metabolic clearance rate based on cytochrome P450 (CYPs) was comparable. In FEK‐SAPH culture, the expression level of the biliary efflux transporter bile salt export pump increased by 230.7%, while the biliary excretion index value of deuterium‐labeled sodium taurocholate (d8‐TCA) differed slightly from the SC value (72% and 77%, respectively, p  = .0195). The inhibitory effect of cholestasis drugs on FEK‐SAPH was significantly higher than that of SC. In FEK‐SAPH, hepatoprotective drugs were more effective in antagonizing hepatotoxicity induced by lithocholic acid (LCA). FEK‐SAPH cultured RPH with hepatoprotective drugs can better recover from LCA‐induced damage. In summary, FEK‐SAPH can be used as a substitute for SC for pharmacokinetic screening to evaluate the drug absorption, disposition, metabolism, excretion, and toxicity (ADMET) in hepatocytes.